Language as mechanism of systemic foundation: Tungus-speaking groups in the Far East. Issue 1 (2nd January 2016) - Mamontova, N.
Abstract : This article explores S. M. Shirokogoroff's critical approach to the study of language as a part of culture and a means of scientific classifications of mankind into a certain number of linguistic categories. The purpose of this article is to highlight a peculiar but rather underestimated contribution of Shirokogoroff to sociolinguistics, as his ideas were often stranded in critical relation to much that was dominant in social and linguistic thought in the first part of the twentieth century. Three dimensions of his work are mainly the focus of this article: the Ural-Altaic hypothesis, linguistic classifications, and the creation of standard languages in Soviet Russia. Finally, it discusses the applicability of Shirokogoroff's critique to the contemporary Russian nationalities' policy towards indigenous minorities.